SENGKETA EKONOMI SYARI’AH DAN KESIAPAN PERADILAN AGAMA - Halim Muhamad Sholeh, Abdul (Jurnal Bimas Islam, 2015)
Abstract The rapid growth of Shariah economic assets in Indonesia raises a logical consequence for increasing economic disputes Shari'ah. Shari'ah economic dispute resolution through the courts is the absolute authority of the Religious Court. This is confirmed by the Law No. Court Decision No. 3/2006 and 93 / PUU-X / 2012. To be able to perform well in order to resolve economic disputes Shari'ah potentially increase in the Religious, the readiness of the Institute of Justice Religion is the absolute thing that must be strengthened. Based on the results of the study in this article, the Institute for Religious Courts--although not yet maximum? it has been sufficiently prepared to handle economic disputes Shari'ah. Readiness includes the readiness of facilities aspects, human resources aspects, and the rules / laws aspects. However, it still needs to be improved readiness by completing the religious courts as a means of additional board space curator for the settlement of disputes bankrupt; increase the number of judges who are certified in the handling of economic disputes Shari'ah, and as soon as possible to legalize a draft compilation of economic events shari'a law in order to serve as guidelines in case areas of economic news events Shari'ah.   Abstraksi Pesatnya pertumbuhan aset ekonomi syari?ah di Indonesia menimbulkan konsekuensi logis bagi meningkatnya sengketa ekonomi syari?ah. Penyelesaian sengketa ekonomi syari?ah melalui jalur pengadilan merupakan wewenang absolut Pengadilan Agama. Hal ini dikukuhkan dengan UU No. 3/2006 dan Putusan MK No. 93/PUU-X/2012. Agar dapat melaksanakan tugas dengan baik dalam rangka menyelesaikan sengketa ekonomi syari?ah yang berpotensi meningkat di Pengadilan Agama, maka kesiapan Lembaga Peradilan Agama merupakan hal mutlak yang harus diperkuat. Berdasarkan hasil kajian dalam artikel ini, Lembaga Peradilan Agama ?meskipun belum maksimal? telah cukup siap untuk menangani sengketa ekonomi syari?ah. Kesiapan itu meliputi kesiapan dari aspek fasilitas, aspek sumber daya manusia, dan aspek peraturan/hukum. Meski demikian, kesiapan itu masih perlu ditingkatkan dengan melengkapi sarana dalam pengadilan agama seperti penambahan ruang dewan kurator untuk penyelesaian sengketa pailit; menambah jumlah hakim yang bersertifikat dalam penanganan sengketa ekonomi syari?ah, serta sesegera mungkin melegalkan draf kompilasi hukum acara ekonomi syari?ah agar dapat menjadi pedoman dalam berita acara bidang perkara ekonomi syari?ah.